2013
DOI: 10.1093/jrr/rrt061
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide radicals in removal of hyper-radiosensitivity by priming irradiation

Abstract: In this study, a mechanism in which low-dose hyper-radiosensitivity (HRS) is permanently removed, induced by low-dose-rate (LDR) (0.2–0.3 Gy/h for 1 h) but not by high-dose-rate priming (0.3 Gy at 40 Gy/h) was investigated. One HRS-negative cell line (NHIK 3025) and two HRS-positive cell lines (T-47D, T98G) were used. The effects of different pretreatments on HRS were investigated using the colony assay. Cell-based ELISA was used to measure nitric oxide synthase (NOS) levels, and microarray analysis to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 60 publications
(79 reference statements)
3
40
1
Order By: Relevance
“…We have previously shown that NO is involved in the response to LDR irradiation (Edin et al 2013). Attempts to measure NO levels in LDR-primed cells have been tried extensively in our laboratory but have failed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that NO is involved in the response to LDR irradiation (Edin et al 2013). Attempts to measure NO levels in LDR-primed cells have been tried extensively in our laboratory but have failed.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were grown as monolayer cultures in RPMI (Roswell Park Memorial Institute) 1640 medium (JRH Biosciences, Kansas, USA), supplemented with 10% fetal calf serum (Gibco, Paisley, UK), 2 mM L-glutamine (Sigma, St Louis, MO, USA), 200 units l 21 insulin (SIGMA), and 1% penicillin/streptomycin (Gibco) at 37°C in air containing 5% CO 2 (Edin et al 2012(Edin et al , 2013. The cells were grown as monolayer cultures in RPMI (Roswell Park Memorial Institute) 1640 medium (JRH Biosciences, Kansas, USA), supplemented with 10% fetal calf serum (Gibco, Paisley, UK), 2 mM L-glutamine (Sigma, St Louis, MO, USA), 200 units l 21 insulin (SIGMA), and 1% penicillin/streptomycin (Gibco) at 37°C in air containing 5% CO 2 (Edin et al 2012(Edin et al , 2013.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The protective effect vanished if the priming irradiation time was reduced to 15 minutes. 26 In the experiments with reporter cells exposed to serum from irradiated mice, the effect was also seen for 3 cGy/h. 24 The effect seems thus to be dose independent as long as the dose rate is within a certain window and the irradiation time is long enough.…”
Section: Discussionmentioning
confidence: 91%